A Creation of Bamboo Products to Add Values for Namsong Community in Payuhakiri District, Nakhon Sawan Province - Manee-oud, Pennapa (Journal of Community Development Research (Humanities and Social Sciences); Vol 11 No 3 (2561): July-September 2018, 2018)
การวิจัยครั้งนี้มีวัตถุประสงค์เพื่อศึกษาข้อมูลไม้ไผ่และสร้างสรรค์ผลิตภัณฑ์จากไม้ไผ่ที่เพิ่มมูลค่าให้กับชุมชนตำบลน้ำทรง อำเภอพยุหะคีรี จังหวัดนครสวรรค์ และเพื่อประเมินความพึงพอใจจากผู้ที่สนใจผลิตภัณฑ์ไม้ไผ่ เครื่องมือที่ใช้ในการวิจัยครั้งนี้เป็นแบบสัมภาษณ์และแบบสอบถาม การวิเคราะห์ข้อมูลจากเอกสารโดยนำข้อมูลที่ได้มาวิเคราะห์สรุปตามประเด็น ได้แก่ แนวโน้มผลิตภัณฑ์ คุณสมบัติของผลิตภัณฑ์ และการใช้วัสดุร่วม และวิเคราะห์ข้อมูลโดยการวิเคราะห์ค่าร้อยละ ค่าเฉลี่ย และส่วนเบี่ยงเบนมาตรฐาน ผลการวิจัย พบว่า พันธุ์ไผ่ที่พบมากที่สุด คือ ไผ่สีสุก ซึ่งพบได้ทั่วไปตามพื้นที่ ส่วนมากปลูกไว้ขายลำ ด้านการใช้ประโยชน์จากไม้ไผ่ จากหน่อและลำ ได้แก่ ทำเครื่องมือประกอบอาชีพ เครื่องเรือน เครื่องใช้ในชีวิตประจำวัน ด้านกรรมวิธีการผลิตผลิตภัณฑ์จากไม้ไผ่ประกอบด้วย 2 วิธี คือ ผลิตภัณฑ์จากเส้นตอก และผลิตภัณฑ์จากลำต้นและกิ่ง ด้านความต้องการใช้ผลิตภัณฑ์จากไม้ไผ่ โดยสุ่มตัวอย่างจากผู้สนใจ จำนวน 246 คน พบว่า ความต้องการใช้ผลิตภัณฑ์ประเภทของใช้มากที่สุด      จากนั้นกระบวนการคิดสร้างสรรค์เพื่อกำหนดชนิดผลิตภัณฑ์ตามทฤษฎีการคิดแบบนอกกรอบ และการประเมินความคิดตามทฤษฎีของเดวิส เพอร์กิน ประกอบด้วยจุดประสงค์ โครงสร้าง รูปแบบจำลองและเหตุผลข้อโต้แย้ง สามารถสรุปได้ผลิตภัณฑ์ คือ จักรยานไม้ไผ่ การทำให้เกิดมูลค่าเพิ่มโดยนำชิ้นส่วนจักรยานเก่ามาใช้ร่วมกับไม่ไผ่ และร่วมกันทำต้นแบบจักรยานไม้ไผ่กับคนในชุมชน      ทั้งนี้ ในเขตพื้นที่ตำบลน้ำทรงมีประวัติความเป็นมาที่น่าสนใจ มีทรัพยากรทางธรรมชาติ และมีถนนเส้นทางที่เชื่อมต่อถึงกัน สามารถส่งเสริมให้จัดเส้นทางจักรยานเพื่อการท่องเที่ยวในพื้นที่ด้วยจักรยานไม้ไผ่ โดยการปั่นเพื่อสุขภาพและนันทนาการ ด้านความพึงพอใจจากผู้ที่สนใจ โดยสุ่มตัวอย่างจากผู้สนใจ ใช้สูตรการคำนวณหาขนาดของกลุ่มตัวอย่างของดับบลิวจีคอชแรน โดยกำหนดความเชื่อมั่นที่ร้อยละ 95 สัดส่วนของประชากรที่ต้องการสุ่ม 0.20 ได้จำนวนกลุ่มตัวอย่าง 246 คน ค่าความพึงพอในภาพรวมอยู่ในระดับมาก คำสำคัญ: ผลิตภัณฑ์ไม้ไผ่  ความคิดสร้างสรรค์  เพิ่มมูลค่า  ผลิตภัณฑ์      The main objectives of this research were to study information of bamboo; to create bamboo products adding more values for Namsong Community, Payuhakiri District, Nakhon Sawan province; and to assess the satisfaction of people interested in those bamboo products. The tools used in the research were interview forms and questionnaires. The documentary analysis was conducted by summarizing aspects of product trends, product property and use of co-materials. The data analysis was presented as percentage, Mean and Standard Deviation. The results of the research revealed that Sie-Sook bamboo was generally grown in the area and sold as stalks. The use of bamboo shoots and stalks appeared in working utensils, furniture and household materials used in daily life. The bamboo products consist of two kinds: products made from thin bamboo stripes and those made from stalks and branches. The demands of bamboo products are measured by interviewing 246 samplings who indicated that daily household utensils were mostly needed.      Following the Creative Thinking process in accordance with the ‘Think outside the Box’ theory, together with the thinking assessment, the new conceptual idea transformed the product into a bamboo bicycle. The work was value-added-based research which combined an old bicycle with bamboo together with ideas of people in the community to produce a bamboo bicycle prototype.      As Namsong Sub-District has interesting historical stories, natural resources and roads connected to other areas, it could promote a bicycle route for tourism, health and recreation. This not only adds values to bamboo products by creating bamboo bikes, but also promotes income from tourists for local people. Regarding the satisfaction of people interested in bamboo products, the sample size was at 95% and the population proportion at 0.20. The sampling group was 246 people and the average satisfaction was at a high level. Keywords: Bamboo Product, Creative Thinking, Value Addition, Products